Catalytic hydrogenation of 5-hydroxymethylfurfural to 2, 5-dimethylfuran over Ru based catalyst: Effects of process parameters on conversion and products selectivity. (November 2020) - Feng, Li; Li, Xuhao; Lin, Yinhe; Liang, Yicong; Chen, Yuning; Zhou, Wen
Abstract: Catalytic in-situ hydrogenation of 5-hydroxymethylfurfural (HMF) to 2, 5-dimethylfuran (DMF) has received a great interest in recent years. Different reaction parameters such as catalysts, reaction temperature, time, pressure, solvents and catalyst amount optimized to achieve the highest conversion of HMF and selectivity of the products. The highest conversion of HMF (98%) and selectivity of DMF (97%) were achieved with Ru/ZSM-5 catalyst at 180 °C under ethanol solvent system for 3 h in 250 psi H2 . The high catalytic efficiency was attributed to the oxophilic nature and acidity of catalyst, whereas the selectivity towards DMF was attributed to the Brønsted acidity of Ru/ZSM-5 and its affinity towards the C-O bond. The catalyst exhibited high yield of DMF from in situ hydrogenation of HMF with ethanol as economical hydrogen donor. Reaction mechanism studies revealed that Ru/ZSM-5 is promoting in situ H2 production from ethanol. Catalyst recyclability on HMF conversion and DMF selectivity has examined. Highlights: Catalytic hydrogenation of 5-hydroxymethylfurfural was investigated. High selectivity (97%) of DMF was obtained with higher conversion (98%) of HMF. Ru/ZSM-5 catalyst showed excellence reusability on DMF product selectivity.